1988
DOI: 10.1038/bjc.1988.223
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hormone levels in early gestation of cryptorchid males: a case-control study

Abstract: Summary A case-control study was conducted to assess maternal hormonal factors associated with increased risk of bearing a cryptorchid son. Serum samples were collected during the first trimester of pregnancy from participants in the US Collaborative Perinatal Study. Twenty-five mothers of normal offspring (controls) were individually matched on medical center, age, parity, weight and length of gestation at the time of sampling to women bearing sons who had a diagnosis of cryptorchidism at one year of age or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 27 publications
2
31
1
2
Order By: Relevance
“…It has been hypothesized that high levels of endogenous oestrogens during critical stages of development in utero may increase the risk of cryptorchidism and testicular cancer (Henderson et al, 1979;, and at least three studies have found some evidence for increased oestrogen levels in first compared with later pregnancies (Bernstein et al, 1986;Panagiotopoulou et al, 1990;Key et al, 1996). Other studies also tend to support this hypothesis (McLachlan et al, 1975;Depue, 1984;Brown et al, 1986;Depue et al, 1983;Bernstein et al, 1988).…”
Section: Materials and Methods Cohortmentioning
confidence: 84%
“…It has been hypothesized that high levels of endogenous oestrogens during critical stages of development in utero may increase the risk of cryptorchidism and testicular cancer (Henderson et al, 1979;, and at least three studies have found some evidence for increased oestrogen levels in first compared with later pregnancies (Bernstein et al, 1986;Panagiotopoulou et al, 1990;Key et al, 1996). Other studies also tend to support this hypothesis (McLachlan et al, 1975;Depue, 1984;Brown et al, 1986;Depue et al, 1983;Bernstein et al, 1988).…”
Section: Materials and Methods Cohortmentioning
confidence: 84%
“…Maoris have relatively lower birth weights than white individuals, and their mothers are frequently obese, which is associated with high estrogen levels. [90][91][92] Whereas timing of puberty has a strong association with the age at the peak incidence of testicular cancer, the correlation to cancers of other reproductive organs is less clear. A population-based, case-control study in Australia reported that markers of delayed androgen action, such as delayed growth spurt in puberty, were FIGURE 1 Age-adjusted incidence of testicular cancer related to activity of selected hormones.…”
Section: Testicular and Prostate Cancermentioning
confidence: 99%
“…An increased risk has also been reported for the contralateral descendent testis (Henderson et al 1979), suggesting common risk factors. Some prenatal risk factors seem to be common for both cryptorchidism and testicular cancer, such as high levels of estrogen in the first trimester (Bernstein et al 1988;Cosgrove et al 1977).…”
mentioning
confidence: 99%